ANALYSIS OF THE IMPACT OF ONLINE LEARNING ON THE SUCCESS PROCESS OF CLASS V STUDENTS AT SDN 73/IX SIMPANG SUNGAI DUREN - Bunga Rahmi Putri; Nazurty Nazurty; Eddy Haryanto (Jurnal Mantik, 2022)
The existence of the COVID-19 pandemic has greatly affected life, especially in the field of education, where the learning process which is usually carried out faceto-face must be carried out online. However, online learning cannot always be carried out optimally. Therefore, this study aims to analyze the impact of online learning on the learning success of fifth grade students. This research is a qualitative research with the research subject of teachers and fifth grade students of public elementary school 73/IX Simpang Sungai Duren. The data collection technique in this study was interviews, while data analysis was carried out with the stages of data reduction, data presentation, and drawing conclusions. The results of this study are the implementation of online learning has several obstacles, especially the availability of facilities and infrastructure, as well as the internet.When online learning the teacher can only explain it from the whatsapp group application by doing voice notes only in explaining the material so that students understand what the teacher is saying. With this, the teacher emphasized that the implementation of online learning had not been able to run optimally, especially in mathematics subjects that could not be implemented properly.